2015
DOI: 10.1371/journal.pone.0126095
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Observations and Fatty Acid Composition of Indoor-Cultivated Cordyceps sinensis at a High-Altitude Laboratory on Sejila Mountain, Tibet

Abstract: Cordyceps sinensis, a caterpillar entomopathogenic fungus-host larva complex, is a rare medicinal herb found in the Qinghai-Tibetan Plateau and its surrounding high-altitude areas. The alternation of generations in the life cycle, whatever the fungus or its host insect, requires special growth conditions. However, it is difficult to simulate the growth conditions of C. sinensis, which hinders its artificial cultivation. In this work, the life cycle from the host larva to C. sinensis was observed in an indoor-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Network analysis was applied to investigate these potential microbial interactions in the complex microbial communities [26]. Chinese cordyceps is essentially the outcome of the competition of the entomogenous fungus (H. sinensis) and the other microbial inhabitants in the host insects [13]. Thus, the microbial interactions would in uence the infection, colonization, and growth of H. sinensis, which ultimately related with the occurrence of Chinese cordyceps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Network analysis was applied to investigate these potential microbial interactions in the complex microbial communities [26]. Chinese cordyceps is essentially the outcome of the competition of the entomogenous fungus (H. sinensis) and the other microbial inhabitants in the host insects [13]. Thus, the microbial interactions would in uence the infection, colonization, and growth of H. sinensis, which ultimately related with the occurrence of Chinese cordyceps.…”
Section: Discussionmentioning
confidence: 99%
“…Besides O. sinensis, our previous study also revealed that several physicochemical factors, the soil bacterial and fungal structure, and the network of these factors, are closely related with the occurrence of Chinese cordyceps, manifesting that the soil ecological environment is important for the occurrence of Chinese cordyceps [12]. Observation on the indoor cultivated Thitarodes larva revealed that, although collected from the same sampling site, the fates of these wild larvae varied greatly and a proportion of these larvae eventually formed Chinese cordyceps [13]. Thus, we proposed that, besides external soil factors, the internal factors of the Thitarodes host (such as the entophytic microbes and immune system of Thitarodes) may also contribute to occurrence of Chinese cordyceps.…”
Section: Introductionmentioning
confidence: 92%
“…Indoor CS development from the host larva was observed in a High-Altitude Laboratory on Sejila Mountain, Tibet by LianXian Guo and his group [21], the soil used initially to keep larva was from natural habitat sampled from Sejila Mountain only. Their findings regarded that low temperature incubation increases the level of unsaturated fatty acid content and could promote infection by Hirstutella sinensis which is a responsible fungal to form this organism.…”
Section: Artificial Cultivation Of Csmentioning
confidence: 99%
“…This abnormity may be reasonably explained as follows. To adapt the inclement environments, C. sinensis requires the plentiful polar lipids enriched in polyunsaturated fatty acids, in particular C18:2 for the larger proportion of cellular and subcellular biomembranes [15,34]. We had revealed that the absolute amount of total fatty acids and relative content of C18:2 in polar lipids from C. sinensis were evidently higher than those from its host larva, implying that C. sinensis assimilated polar lipids much more than those in the host larva and had transformed more C18:1 to C18:2 except a direct uptake of C18:2 from the parasitized larva.…”
Section: Stable Carbon Isotope Fractionation In the Lipids Of C Sinementioning
confidence: 99%